The short- and long-term effects of a course on rational drug use: A comparative study between prefinal- and final-year undergraduate medical students who attended the course in different clinical years - AKDENİZ, ESRA; SARIKAYA, ÖZLEM (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
BACKGROUND: Rational pharmacology use and appropriate prescribing are among the key learning outcomes in medical education. Some medical faculties include rational pharmacotherapy course in their education programs at different years of education in Turkey. The aims of this study were to investigate the differences in effect of rational pharmacotherapy course on short- and long-terms by comparing two cohorts who attended the course in different clinical years of medical education by identifying which parameters of prescription items are different among groups. MATERIALS AND METHODS: This quasi-experimental study was conducted in School of Medicine. Participants consisted of 157 students who attended the course in Grade 4 (n = 110, Group A) and Grade 5 (n = 47, Group B). Students were asked to complete a prescribing task both upon completion of the course and 1 year after. The performance in prescribing was determined by prescription scoring form. Repeated measures ANOVA was employed to test the intervention effect between two periods. McNemar test was employed to measure the change in each item on the prescription. Point-biserial correlations between each item on the prescription and their scores on the test as a whole were calculated. RESULTS: The mean score of Group A dropped to 59.41 (standard deviation [SD] = 14.06) from 90.43 (SD = 8.90), and the mean score of Group B dropped to 73.37 (SD = 12.56) from 83.91 (SD = 10.03). All the prescription components in the scripts of the Group A students worsened significantly, except the name of drug, whereas Group B students maintained most of them after 1 year. CONCLUSIONS: This study shows that the long-term retention effect of rational pharmacotherapy course conducted in later years of education is better than the course conducted in earlier years of education, which may be related to the fact that students in later years are more likely to take on responsibility for patient therapy process in clinical education.
Keywords: Clinical competence; drug prescriptions; medical education; pharmacology; quasi-experimental; undergraduate; THERAPEUTICS EDUCATION; PHARMACOLOGY KNOWLEDGE; PRESCRIBING SKILLS; PERFORMANCE; CURRICULUM; DOCTORS; ERRORS